An Information-Theoretic Account of Semantic Interference in Word Production - Futrell, Richard (Frontiers in Psychology, 2021)
I present a computational-level model of semantic interference effects in online word production within a rate--distortion framework. I consider a bounded-rational agent trying to produce words. The agent's action policy is determined by maximizing accuracy in production subject to computational constraints. These computational constraints are formalized using mutual information. I show that semantic similarity-based interference among words falls out naturally from this setup, and I present a series of simulations showing that the model captures some of the key empirical patterns observed in Stroop and Picture--Word Interference paradigms, including comparisons to human data from previous experiments.